Analysis of the Effect of Long-Term Electric Field Treatment on the Spatial Configuration of Fatty Acids in Raw Avocado Oil (Persea americana Mill var. Hass) - José Alberto Ariza-Ortega; María Reyna Robles-López; Raúl René Robles-de-la-Torre (Issues and Development in Health Research Vol. 1, 2021)
The main objective of this study was to evaluate the stability of fatty acids in raw avocado oil when the product is subjected to different electric field treatment conditions (voltage: 5 Kilo-Volts cm-1, frequency: 720 Hertz and treatment time: 5, 10, 15, 20 and 25 min). Fatty acids were analyzed by gas chromatography. The raw avocado oil had a higher concentration of unsaturated fatty acid (83.31%), where oleic (60.6%) was predominated. The elaidic fatty acid content was quantified at a lower percentage (0.01%) than reported by the Food Safety Commission of Japan, Tokyo. The electric field treatment did not affect the concentration and quality of fatty acids in the raw avocado oil.